Outcomes of anemic patients presenting with acute coronary syndrome: An analysis of the Cooperative National Registry of Acute Coronary Care, Guideline Adherence and Clinical Events. Issue 9 (19th June 2019) - Huynh, Ronald; Hyun, Karice; D'Souza, Mario; Kangaharan, Nadarajah; Shetty, Pratap C.; Mariani, Justin; Kilian, Jens; Hung, Joseph; Ryan, Mark; Chew, Derek P.; Brieger, David
Abstract: Background: Anemia commonly accompanies acute coronary syndromes (ACS) and is associated with poorer outcomes. This study examines the associations between anemia, management and outcomes in an Australian ACS population. Methods: This analysis of the CONCORDANCE database included 8665 ACS patients presenting to 41 Australian hospitals. Baseline characteristics, management, and outcomes were compared between patients with anemia (Hb ≤ 130 for males, Hb ≤ 120 g/L for females) and non‐anemia. Results: A total of 1880 (21.7%) patients presenting with ACS were anemic. These patients were older (72 years vs 63 years, P < .0001), with higher prevalence of comorbidities. STEMI patients with anemia were less likely to be emergently reperfused with either thrombolytic therapy (22% vs 33%, P <  .0001) or primary percutaneous coronary intervention (PCI) (45% vs 51% P = 0.033). For all ACS, anemic patients less frequently received: coronary angiography (63% vs 86%, P < .0001); drug eluting stents if undergoing PCI (50% vs 58%, P <  .0001); dual antiplatelet therapy (80% vs 89%, P < .0001) ;and parenteral anticoagulants (82% vs 88%, P < .0001). In hospital complications of heart failure (20% vs 9%, P <  .0001), renal failure (13% vs 4%, P < .0001), and re‐infarction (4% vs 2%, P = .0006) were more common among anemic patients. There was a near‐linear inverse relationship between admission hemoglobin and in hospital mortality. Conclusions: Anemic patients with ACS are a high risk group less likely to undergo invasive and antithrombotic therapy. Further investigation is required to determine if more active treatment of anemic patients presenting with ACS will improve their outcomes.